THE RELATIONSHIP BETWEEN FAMILY FUNCTIONS AND RISKY SEXUAL BEHAVIOR IN INDONESIA IN 2018: A PMA DATA ANALYSIS - Diah Puspita Sari; Mario Ekoriano; Aditya Rahmadhony (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
This analysis aimed to examine the relationship between family development and risky adolescent sexual behavior in Indonesia. The data were taken from the 2018 Performance and Accountability Survey with a family and adolescent questionnaire; thus, the relationship between parents and adolescents could be identified. The statistical analysis methods used were descriptive and inferential analyses, with the unit of analysis being 15,556 teenagers who dated. The results of the logistic regression analysis (Model 1) by using all the independent variables simultaneously found that sexual risk behavior was mostly found in in boys, age categories 20-24 years, and participants who never had access to PIK-R. Risky sexual behavior was also dependent on whether participants agreed to have relations sexual before marriage, and also the level of education of their parents. The logistic regression analysis (Model 2) found residence, gender, level of adolescent education, age categories, agreement to have sexual relations before marriage, age groups of head of family, gender of head of family, education level of head of family, work status of head of family, economic status, and the activeness of the BKR activities contributed to adolescents committing risky sexual behaviors.